The relationship between smile attractiveness and esthetic parameters of patients with lateral agenesis treated with tooth recontouring or implants - De-Marchi LM; Pini NI; Pascotto RC (Dove Medical Press, 2012)
Luciana Manzotti De-Marchi,1 Núbia Inocencya Pavesi Pini,2 Renata Corrêa Pascotto31Department of Dentistry, University Center of Maringá-CESUMAR, Maringá-PR/Brazil; 2Piracicaba Dental School, State University of Campinas, Piracicaba-SP/Brazil; 3Department of Dentistry, State University of Maringá, Maringá-PR/BrazilBackground: The purpose of this study was to associate smile esthetic judgment with dentofacial attributes of patients with unilateral and bilateral agenesis of maxillary lateral incisors treated with recontouring of canines or implants and patients with no agenesis (control).Material and methods: Forty-six participants were divided into two groups: those treated with recontouring (N = 26) and those treated with implants (N = 20). The participants in the control group (N = 22) were selected among dentistry students at the State University of Maringá, Brazil. Photographs of posed smiles (17 cm × 10 cm) were evaluated with a 100-mm Visual Analog Scale. Smile attractiveness was judged by two groups: laypersons and dentists (N = 20 in each group). Judgment was classified into Unpleasant and Pleasant. Measurements of 11 smile attributes were done with ImageTool Version 3.0. These measurements were correlated with the type of judgment using the Pearson correlation coefficient.Results: The two groups of evaluators showed no rating difference (analysis of variance, P = 0.64), thus they were placed into a single group. No significant correlation was found between esthetic judgment and six smile attributes (incisor exposure, interlabial gap, width 3 to 3, smile index, right buccal corridor, and buccal corridor ratio). The control group showed more correlations with the unpleasant judgment type than the other groups.Conclusion: Some correlations between smile attributes and esthetic judgment were found, but other features of smiles not evaluated in this study may interfere in smile attractiveness.Keywords: esthetic, dental agenesis, attractiveness, dental implants, composite resin, perception